Role of Entrepreneurial Culture as the Driver of Economic Growth - Prasetyo, P. Eko (International Journal of Economics and Financial Issues, 2019)
The role and function of entrepreneurial culture get more important and is the main driver of sustainable regional and national economic growth in Indonesia. The specific purpose of this article is to explain the role of entrepreneurial culture as the driver of regional economic growth in Central Java, Indonesia. For the purpose of this research, a survey for primary data and recursive model of path analysis are employed. The research results show positive and significance influence of entrepreneurial culture and network as well as competition on regional economic growth. With the principle of “tuna satak bati sanak” culture as the basic behavioral pattern of their business, the social entrepreneurial network and entrepreneurial culture in the research area are strengthened. Therefore, with support of entrepreneurial culture, the growth of entrepreneurship in Indonesia will serve more to be the main driver of sustainable economic growth. Keywords: entrepreneurial culture, network, competition, and regional economic growth JEL Classifications: D91, L31, L51 DOI: https://doi.org/10.32479/ijefi.7882